I. Design and Synthesis of Α6-GABAAR Subtype-selective Pyrazoloquinolinones with Improved Metabolic Stability and Enhanced Bioavailability. II & III. Process Development of Subtype-Selective Α2/3-GABAAR Imidazodiazepines: HZ-166 and KRM-II-81 and Α5-GABAAR Imidazodiazepines: MIDD0301 and GL-II-73 - (:unkn) unknown (My University, 2020)
Abstract-Part 1 Examination of recent reports indicate that α6β2/3γ2 GABAAR selective ligands may be important for the treatment of trigeminal orofacial pain and neuropsychiatric disorders with sensori-motor gating deficits. Based on 3 functionally α6β2/3γ2 GABAAR selective pyrazoloquinolinones, 49 novel analogs were synthesized and their in vitro metabolic stability and cytotoxicity, as well as their in vivo pharmacokinetics, basic behavioral pharmacology, and effects on locomotion were investigated. Incorporation of deuterium into the methoxy substituents of the ligands increased their duration of action via improved metabolic stability and bioavailability, while their selectivity for the GABAAR α6 subtype was retained. The deuterated pyrazoloquinolinone DK-I-56-1 (8b) was identified as the lead compound with a substantially improved pharmacokinetic profile. The ligands allosterically modulated diazepam insensitive α6β2/3γ2 GABAARs and were functionally silent at diazepam sensitive α1β2/3γ2 GABAARs, thus no sedation was detected. In addition, these analogs were not cytotoxic, which rendered them interesting candidates for treatment of CNS disorders mediated by GABAAR α6β2/3γ2 subtypes. Recently, the GABAAR α+β- binding site was discovered along with the first α6-GABAAR subtype-selective ligand, PZ-II-029 (8a) and later, LAU463 (8n). Subsequent research led to the development of the lead deuterated pyrazoloquinolinones, DK-I-56-1 (8b), DK-I-58-1 (8o) and DK-II-58-1 (13h) which have been shown to exhibit functional selectivity for α6-GABAARs with increased metabolic stability and enhanced bioavailability. The pursuit of further improvements to the bioavailability of these α6-selective ligands led to the exploration of fluorinated substituents (trifluoromethoxy) as an alternative tactic to limit O-demethylation in vivo of the methoxy groups of these lead ligands DK-I-56-1 (8b) and DK-I-58-1 (8o). Herein, the comparative in vivo and in vitro effects of deuteration versus fluorination of these pyrazoloquinolinones is reported. While the strategy of deuteration and fluorination both increased metabolic stability in HLM and MLM, the pharmacokinetic effect on plasma, brain, liver and kidney exposure was dramatically different. Additionally, the fluorinated analogs exhibited a slightly increased cytotoxic effect in vitro on liver and kidney cell lines. Efficacy and functional selectivity for the α6+β3- interface (PQ Site) of α6-GABAARs was reduced for the fluorinated analogs in comparison to the deuterated ligands, as was as the binding affinity at the Bz site (α+γ- interface). In summary, the deuteration strategy proved superior to fluorination of these pyrazoloquinolinones in terms of maintaining α6-selectivity while enhancing the bioavailability and drugability of these α6-GABAAR ligands without detrimental effects. Finally, a more water-soluble phosphoric acid prodrug of DK-I-58-1 (8o) was also synthesized. Part 2 The need for improved medications for the treatment of epilepsy and chronic pain is essential. Epileptic patients typically take multiple antiepileptic drugs without complete seizure freedom. The (5-(8-ethynyl-6-(pyridin-2-yl)-4H-benzo[f]imidazole[1,5-[1,4]diazepin-3-yl) oxazole (KRM-II-81) is a lead compound in a series of ligands designed as positive allosteric modulators (PAMs) of 2/3-containing GABAA receptors. Ligand KRM-II-81 produced broad-based anticonvulsant efficacy in rodent models used to predict antiepileptic efficacy in patients and provides a wider margin over motoric side effects than that of other GABAA receptor PAMs. The present series of experiments was designed to fill key missing gaps in prior preclinical assessments to assess whether KRM-II-81 could be further differentiated from non-selective GABAA receptor PAMs using the anticonvulsant diazepam (DZP) as a comparator. In multiple chemical seizure provocation models in mice, KRM-II-81 was either equally or more efficacious than that of DZP. In addition, KRM-II-81 but not DZP blocks the development of seizure sensitivity to the chemical convulsants cocaine and pentylenetetrazol. This antiepileptogenic effect is considered the holy grail of antiepileptic treatment. These and previous data have placed KRM-II-81 into consideration for clinical development requiring the manufacture of kilogram amounts of GMP material. We describe here a novel synthetic route amenable to kilogram quantity production. The new biological and chemical data provide key steps forward in the development of KRM-II-81 for patients who continue to suffer from pharmacoresistent epilepsy. Part 3 MIDD0301 ((R)-8-bromo-6-(2-fluorophenyl)-4-methyl-4H-benzo[f]imidazo[1,5-a][1,4]diazepine-3-carboxylic acid) is a novel oral drug under development for the treatment of asthma, which targets peripheral α5-GABAARs found in airway smooth muscle (ASM) and reduces lung inflammation. Because of the promising results of MIDD0301 as an asthma therapy devoid of negative side effects, the need for clinical development was of interest. Consequently, the development of a synthetic procedure amenable to the GMP manufacture of kilograms quantities of MIDD0301 was required to improve upon the discovery route. Described herein is an improved and novel synthetic route amenable to the production of kilogram quantities of MIDD0301. Over the last 15 years worldwide life expectancy increased by 5 years jumping from 66 years to 71 years. With progress in science, medicine, and care one tends to live longer. Such extended life expectancy is still associated with age-related changes, including in the brain. The aging brain goes through various changes that can be called morphomolecular senescence. Overall, the brain volume changes, neuronal activity is modified, and plasticity of the cells diminishes, sometimes leading to neuronal atrophy and death. Altogether, these changes contribute to the emergence of cognitive decline where upon an efficient treatment is still not available. Many studies in the context of cognitive decline focused on pathological aging, targeting beta-amyloid in Alzheimer's disease, for example. However, beta-amyloid plaques are also present in healthy adults and treatments targeting plaques have failed to improve cognitive functions. In order to improve the quality of life of aging populations, it is crucial to focus on the development of novel therapies targeting different systems altered during aging, such as the GABAergic system. In previous studies it has been shown that positive allosteric modulators (PAM) acting at α5-containing GABAA receptors improve cognitive performances, and that these α5-GABAA receptors are implicated in dendritic growth of pyramidal neurons. Here, we hypothesized that targeting the α5-GABAA receptors could contribute to the reduction of cognitive decline, directly through activity of the receptors, and indirectly by increasing neuronal morphology. Using primary neuronal culture and chronic treatment in mice, it was demonstrated that an α5-PAM (GL-II-73) increased dendritic length, spine count and spine density in brain regions involved in cognitive processes (prefrontal cortex and hippocampus). The pro-cognitive efficacy of the α5-PAM, GL-II-73 was confirmed and the washout period diminished the precognitive effects without altering the effect on neuronal morphology. Future studies will be needed to investigate what downstream mechanisms are responsible for the neurotrophic effect of the α5-PAM (GL-II-73). These results and previous data have placed GL-II-73 into consideration for clinical development requiring a route to manufacture of kilogram amounts of GMP material. Described herein is a novel synthetic route amenable to kilogram quantity production.